CHEMICAL ABUNDANCES IN GALACTIC HII REGIONS - PEIMBERT, M; COSTERO, R (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1969)
New photoelectric observations of Orion, M8, and M17 are presented; from these data the chemical abundances of He, C, N, O, Ne, and S with respect to hydrogen are derived, taking into account the effect of temperature fluctuations over the volumes conside
BOL OBS TONAN TACUB
Keywords: CHEMICAL, ABUNDANCES, GALACTIC, HII, REGIONS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS